Development of recombinant adenovirus vector herpes zoster vaccine production process using perfusion strategy with tangential flow filtration system. Issue 2 (14th November 2022) - Sun, Yang; Feng, Kai; Nie, Jianqi; Huang, Lingling; Liu, Yupeng; Bai, Zhonghu
Abstract: BACKGROUND: Herpes zoster (HZ) causes painful skin and nerve lesions, and its most frequent complication is postherpetic neuralgia. Currently, vaccination is recommended to decrease the incidence of HZ, and cost‐effective vaccine production strategies are required to produce low‐cost vaccines. Perfusion cultivation is now a common trend for increasing bioreactor productivity and overcoming nutritional limitations. The tangential flow filtration (TFF) system has proven to be suitable for perfusion cultures of mammalian cells. However, perfusion cultivation exponentially increases medium consumption, and a proper perfusion strategy should be developed to supply nutrition and save medium at the same time. RESULTS: In this study, an HEK 293 cell‐based recombinant adenovirus vector herpes zoster (rAdV‐HZ) vaccine production process was developed using a novel TFF perfusion system. First, the perfusion start time, perfusion rate, and glutamine concentration were investigated in shake flasks to increase the cell density with an economical perfusion strategy. Then, the key process parameters (cell concentration at infection, multiplicity of infection, and virus production media) of the rAdV‐HZ production process were optimized using the design of experiments approach, and the robust setpoint and design space of the key process parameters were obtained. Finally, the process parameters at the robust setpoint were successfully scaled up to a 7 L bioreactor with a novel TFF system, yielding an rAdV‐HZ titer of 1.7 × 10 10 infectious units mL −1 . CONCLUSION: This study can serve as a baseline for developing an economical perfusion strategy for the large‐scale production of recombinant adenovirus vector‐based vaccines. © 2022 Society of Chemical Industry (SCI).